The influence of glycerol on the binding of methotrexate to Mycobacterium tuberculosis dihydrofolate reductase: a molecular modelling study - Hong, W.; Chang, Z.; Wang, Y.; Sun, T.; Pu, J.; Paterson, I.C.; Wang, H. (2015)
The enzyme, dihydrofolate reductase (DHFR), from Mycobacterium tuberculosis (mt-DHFR) is believed to be a potential drug target for the treatment of tuberculosis. The co-crystal structure of mt-DHFR bound with glycerol (GOL), NAPDH and methotrexate (MTX) reveals a GOL binding site on the enzyme. This GOL binding site could be very important for the design of novel, selective mt-DHFR inhibitors, because this binding site is absent on human DHFR (h-DHFR). We have performed molecular dynamic simulations and free energy calculations to evaluate the binding affinity of GOL and its free energy contribution to the binding of MTX to mt-DHFR. The results showed that GOL does not bind tightly to mt-DHFR. Although GOL itself contributed free energy on MTX binding to mt-DHFR, GOL also increased the flexibilities of MTX, so that MTX cannot maintain strong electronic interactions with ARG32 and ARG60, which caused the total binding free energy to decrease. These data suggest that GOL binding is weak and it could be expelled from the binding site, to allow inhibitors containing appropriate side chains to bind. This observation can be used to inform future drug design studies, especially those aimed at improving drug selectivity against h-DHFR.